2022
DOI: 10.1111/bcp.15438
|View full text |Cite
|
Sign up to set email alerts
|

Statin‐related adverse drug reactions in UK primary care consultations: A retrospective cohort study to evaluate the risk of cardiovascular events and all‐cause mortality

Abstract: To investigate the risk of cardiovascular disease (CVD) events and all-cause mortality in patients with statin-related adverse drug reaction (ADR) consultation in primary care and examine whether different treatments following the ADR affect subsequent outcomes.Methods: This was a retrospective cohort study of statin users between 2004 and 2019 using IQVIA Medical Research Data (formally known as the THIN database).Patients with statin-related ADR consultation were matched by propensity score(1:1) to statin us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Previous studies have reported that ADRs related to other cardiovascular drugs increased the risk of adverse cardiovascular outcomes. 20 , 26 In addition, a study by Albani et al , which focused on patients with a history of acute coronary syndrome, showed that the intolerance to medications used for secondary CVD prevention, including ACEIs/ARBs, was independently associated with recurrent CVD events; 39 this is consistent with the findings of the study presented here. Schmidt et al showed that elevated creatinine levels of ≥30% following ACEI/ARB use were associated with CVD events, mortality, and end- stage renal diseases.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Previous studies have reported that ADRs related to other cardiovascular drugs increased the risk of adverse cardiovascular outcomes. 20 , 26 In addition, a study by Albani et al , which focused on patients with a history of acute coronary syndrome, showed that the intolerance to medications used for secondary CVD prevention, including ACEIs/ARBs, was independently associated with recurrent CVD events; 39 this is consistent with the findings of the study presented here. Schmidt et al showed that elevated creatinine levels of ≥30% following ACEI/ARB use were associated with CVD events, mortality, and end- stage renal diseases.…”
Section: Discussionsupporting
confidence: 89%
“…ACEI/ARB-related ADRs were observed in ∼1% of users of ACEIs/ARBs, which is a lower rate than that of previous studies (up to 3.9%); 13 , 14 this may be due to variability in ADR assessment and/or recording. 26 , 27 In addition, the severity of ADRs addressed in the consultations could not be identified, which might have affected the decision to continue or discontinue the medication. However, a previous systematic review estimated that the majority of ADRs in the primary care setting were of mild- to-moderate severity, compared with those requiring urgent medical care or hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations